Paritisipasi Politik Gen Z: Eksplorasi Peran Media Sosial dalam Pembentukan Kesadaran Politik Remaja - Putra, T. Rivaldo; Wahyuni, Ririn Tri; Meilani, Nayla; Anjani, Mutiara; Sari, Dian Kumala (Jurnal Pendidikan Kewarganegaraan dan Politik, 2024)
The millennial generation, also known as Generation Y, includes those born between 1981 and 2000 and currently aged 18 to 37 years. In the context of elections and politics, social media significantly influences how millennials and Generation Z (born between the mid-1990s and early 2000s) obtain information and participate. This study aims to provide insights for election organizers and political parties on effectively using social media for political education among Generation Z. By understanding their media usage patterns and preferences, political information can be better packaged to ensure broader political awareness among youth. Generation Z is notably open to social and environmental issues and often uses social media to voice opinions and drive change. Despite the prevalence of misinformation and unclear campaigns on social media, which deter some youth from political participation, this research underscores the importance of engaging young people in politics. Using qualitative methods, including direct observation and interviews, the study investigates how social media shapes the political participation and awareness of Generation Z, particularly in Pekanbaru. The results indicate that social media plays a crucial role in providing political information and fostering political engagement among youth.